Peran Kepala Sekolah dalam Meningkatkan Sarana dan Prasarana Pendidikan di SDIT Insani Islamia Bekasi - APRIYANTI WIDIANSYAH (Cakrawala - Jurnal Humaniora, 2018)
This study research aimed to determine: (1) the headmaster's role in improving the management of educational facilities at Insani Islamia Integrated Islamic Elementary School Tambun Bekasi; (2) the headmaster’s strategy in improving the management of educational facilities at Insani Islamia Integrated Islamic Elementary School Tambun Bekasi.This research was in April to May 2016 at Insani Islamia Integrated Islamic Elementary School Tambun Bekasi. The subjects were the headmaster’s and III grade and V grade class teachers. Data collection techniques used observation, interviews and documentation. Data were analyzed by qualitative descriptive of data reduction, data presentation, and conclusion or information. The examination of the validity of data used a test of the credibility of the triangulation consisted of source triangulation and triangulation techniques, dependability test, and confirmability test.